Maternal health associated with exclusive breastfeeding ENDES 2021-2023 - Alva Huapaya, Mariafernanda (2024)
Introduction: Exclusive breastfeeding (EBF) is essential for infant development during the first six months of life, providing nutritional and immunological benefits for both the newborn and the mother. Objective: To determine the association between maternal health and EBF in Peru, based on data from the ENDES 2021-2023. Materials and Methods: A retrospective analytical cross-sectional study was conducted using data from ENDES 2021-2023. The study population included mothers of children under six months of age. The dependent variable was EBF, while independent variables included maternal age, region of residence, difficulty concentrating, appetite distortion, type of delivery, prenatal care, and breastfeeding training. A Poisson regression model with robust variance was used, reporting adjusted prevalence ratios with 95% confidence intervals (CI95%). Results: Maternal age and region of residence were significantly associated with EBF. Difficulty concentrating reduced the probability of practicing EBF by 5% (PR=0.95; CI95%=0.92-0.99; p=0.015), while cesarean delivery decreased it by 6% (PR=0.94; CI95%=0.90-0.98; p=0.006). In contrast, breastfeeding training increased the likelihood of EBF by 7% (PR=1.07; CI95 %=1.04-1.12; p<0.001). Conclusion: Factors such as maternal age, region of residence, cesarean delivery, difficulty concentrating, and training are significantly associated with EBF. Strengthening postpartum support strategies is recommended to improve adherence to EBF in Peru.